2016
DOI: 10.18632/oncotarget.11769
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging to evaluate malignant potential of IPMNs

Abstract: ObjectiveTo investigate using quantitative imaging to assess the malignant potential of intraductal papillary mucinous neoplasms (IPMNs) in the pancreas.BackgroundPancreatic cysts are identified in over 2% of the population and a subset of these, including intraductal papillary mucinous neoplasms (IPMNs), represent pre-malignant lesions. Unfortunately, clinicians cannot accurately predict which of these lesions are likely to progress to pancreatic ductal adenocarcinoma (PDAC).MethodsWe investigated 360 imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 22 publications
4
60
0
3
Order By: Relevance
“…showed the potentiality of texture analysis to discriminate benign and malignant IPMNs with an AUC of 0.77. Hanania et al . have also drawn similar conclusion with 34 high‐risk and 19 low‐risk IPMN patients which are consistent with the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…showed the potentiality of texture analysis to discriminate benign and malignant IPMNs with an AUC of 0.77. Hanania et al . have also drawn similar conclusion with 34 high‐risk and 19 low‐risk IPMN patients which are consistent with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In a concept-of-proof study with 38 patients, including 20 benign and 18 malignant IPMNs, Permuth et al 19 showed the potentiality of texture analysis to discriminate benign and malignant IPMNs with an AUC of 0.77. Hanania et al 18 have also drawn similar conclusion with 34 high-risk and 19 lowrisk IPMN patients which are consistent with the present study. However, all these methods were investigated with small sample sizes.…”
Section: Discussionsupporting
confidence: 91%
“…Image biomarker explorer is an open‐source tool for radiomic feature calculation made available by the MD Anderson Cancer Center, and it has already been reliably used for radiomic studies by several institutions around the world . Recently, a paper was published that shares guidelines and experiences using this software .…”
Section: Methodsmentioning
confidence: 99%
“…Image biomarker explorer is an open-source tool for radiomic feature calculation made available by the MD Anderson Cancer Center, and it has already been reliably used for radiomic studies by several institutions around the world. [27][28][29][30][31][32][33] Recently, a paper was published that shares guidelines and experiences using this software. 34 Image biomarker explorer allows the straightforward calculation of eight feature categories: shape, intensity direct, intensity-histogram, intensityhistogram Gaussian fit, gray-level co-occurrence matrix, gray-level run length matrix, neighborhood gray tone difference matrix, and gradient orient histogram.…”
Section: Methodsmentioning
confidence: 99%
“…Since only 15–20% of BD‐IPMN will develop malignancy and nonsurgical management is recommended for low‐risk BD‐IPMNs, we need to correctly identify malignant IPMNs. Recently, an imaging tool that is combined with the identification of genomic patterns, coined ‘radiomics’, has been proposed by several studies (Hanania et al ., ; Permuth et al ., ). Similarly, Berger et al .…”
Section: Clinical Application Of Ctdna In Pdacmentioning
confidence: 97%